BANKS IN LIBYA, HOW THEY STARTED, HOW THEY WERE LIBYANISED, AND SOME PROPOSALS - البيه , د.عبد المنعم (Dirasat in Economics and Business, 1970)
The following abastracts are short synopses of articles appearing in the Arabic part of the Rovlew. They are summarized here for the benefit of those who cannot read Arabic.in a like manner, each major English or French article is presented As a short résumé in the Arabic section.